Investigation the Influence of Stress on Salivary Features, Oral Hygiene and Gingival Health Condition among a Group of Adolescents Male Students - Assawer Ahmed Al-awadei; Alhan Ahmed Qasim (مجلة الكوفة الطبية)
Background: Stress is a condition that causes pressure and is caused by several factors in teens, such as unplanned events. Subjects and Method: This observational comparative study included 260 male students divided into three groups: low stress, moderate stress, and high stress who were provided according to the Adolescent Stress Questionnaire Scale (ASQ-S). Oral hygiene examination, including plaque index, was done according to Silness and Loe,1964 index, and calculus examination was done according to Ramfjord,1959 index, while gingival health examination was performed according to Loe and Silness,1967 index. Salivary pH, flow rate, salivary Vitamin B₁₂, and Folic acid were measured in unstimulated saliva samples from the low and high-stress groups. Results: It has been shown that the higher means of plaque and gingival indices among high-stress level students was statistically non-significant (p>0.05). The high-stress group has a reduced salivary flow rate, with significant differences (P ˂ 0.05). Vitamin B₁₂ and Folic acid levels were more critical in the high-stress group (P > 0.05). Among both low and high-stress groups, there was a negative, non-significant correlation between pH and flow rate with plaque and gingival indices. In high-stress students, the correlation of Vitamin B₁₂ and Folic acid with plaque and gingival index was damaging. Conclusion: Augmentation of stress is linked with disturbance of psychological well-being, which tends to influence oral hygiene and gingival health by lowering the rate of saliva flow and impacting the levels of Vitamin B₁₂ and Folic acid in saliva.